Influence of Bedding Planes on the Mechanical Characteristics and Fracture Pattern of Transversely Isotropic Rocks in Direct Shear Tests - Lei Xia; Yawu Zeng; Rong Luo; Wei Liu (Shock and Vibration)
Bedding planes are the primary control on the anisotropy of mechanical characteristics and fracture patterns in rock. To analyze the influence of the geometrical properties of bedding planes on the direct shear strength characteristics and fracture patterns of transversely isotropic rocks, numerical models were established using an improved modeling method using Particle Flow Code. The results of the numerical model were in good agreement with those of the physical experiments of an artificial rock mass containing a single bedding plane. The results show that the shear fractures with a range of bedding plane geometries can be divided into two patterns. When the inclination angles of the bedding planes were larger or smaller, a thoroughgoing fracture plane was formed near the preexisting shear fracture plane. On the other hand, the intact rock was broken into many parallel sheets.